Curriculum Approach used in Teaching English : A Case Study - Elda Selja Putri; Absharini Kardena (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2022)
The development and implementation of language teaching programs can be approached in several different ways, each of which has different implications for curriculum design. Indonesian schools have started modernizing their curricula by adopting a backward design that places an emphasis on students' learning outcomes in order to replace the outdated forward paradigm. They must, however, overcome a difficulty in order to achieve a beneficial alignment. This problem spurred a case study examination of the primary curriculum's objectives, syllabus, methodology, and evaluation. The results of the research indicate that the curriculum was created forward, despite claims that it was designed backward, with learning outcomes acting as program goals. In truth, the one that follows it promotes the exchange of knowledge above the development of skills. Since they still relied on information transmission, the program's learning goals were not linked with the three important components of syllabus, methodology, and assessment. The university's innovation of technique including a transfer in emphasis from the lecturer to the students was nonetheless rigidly and mechanically interpreted, and the assessment of student learning was said to be criterion-referenced without more explanation for each syllabus.